2021
DOI: 10.1007/s00296-021-05030-y
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of multisystem inflammatory syndrome in children temporally related to COVID-19: a longitudinal study

Abstract: To study the clinical, laboratory characteristics and outcomes of multisystem inflammatory syndrome in children (MIS-C) temporally related to coronavirus disease 2019 (COVID-19) in a resource-limited setting. All children meeting the World Health Organization case definition of MIS-C were prospectively enrolled. Baseline clinical and laboratory parameters were compared between survivors and non-survivors. Enrolled subjects were followed up for 4–6 weeks for evaluation of cardiac outcomes using echocardiography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 23 publications
6
39
8
1
Order By: Relevance
“…This is in agreement with the epidemiology of MIS-C, which indicates that majority of the cases develop 4–6 weeks after exposure to the virus ( 27 ). In our study, 23.9% had underlying co-morbidities, whereas it was 38.7% in the previous Indian study ( 13 ), 28.35% in Turkish study ( 26 ), and 15.8% in the Latin American study ( 24 ).…”
Section: Discussioncontrasting
confidence: 72%
See 4 more Smart Citations
“…This is in agreement with the epidemiology of MIS-C, which indicates that majority of the cases develop 4–6 weeks after exposure to the virus ( 27 ). In our study, 23.9% had underlying co-morbidities, whereas it was 38.7% in the previous Indian study ( 13 ), 28.35% in Turkish study ( 26 ), and 15.8% in the Latin American study ( 24 ).…”
Section: Discussioncontrasting
confidence: 72%
“…In our study, rash was reported in 40% cases compared to 57.14% in the previous Indian study ( 12 ), 68% in the Brazilian study ( 25 ), and 54.9% in a systemic review ( 12 ). Our study reported a higher rate of non-purulent conjunctivitis (71%) compared to 25.8% in the Indian study ( 13 ), 31.3% in the Turkish study ( 26 ), and 49.8% reported in the systematic review ( 12 ).…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations